Peran Iklim Organisasional dalam Memoderasi Pengaruh Kecerdasan Emosional dan Komitmen Afektif terhadap Kinerja Karyawan Generasi Z pada Sektor Perbankan - Angga Amlisio Perdana; Mega Asri Zona (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Employee performance is one of the key determinants of organizational success, particularly in the banking sector, where service quality and organizational competitiveness depend heavily on human resources. Generation Z employees possess distinctive characteristics that require organizations to consider psychological and organizational factors in improving their performance. This study aims to analyze the effects of emotional intelligence and affective commitment on employee performance, with organizational climate serving as a moderating variable. The research employed a quantitative approach using a causal explanatory design. Data were collected from 103 Generation Z employees working in the banking sector in Padang City, West Sumatra, through a structured questionnaire. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings reveal that emotional intelligence has a positive and significant effect on employee performance, whereas affective commitment does not have a significant direct effect on employee performance. Furthermore, organizational climate significantly moderates the relationship between emotional intelligence and employee performance with a negative direction, while positively moderating the relationship between affective commitment and employee performance. These findings indicate that a supportive organizational climate does not always strengthen the influence of psychological factors on employee performance but may produce different moderating effects depending on the relationship examined. This study contributes to the development of Affective Events Theory by providing empirical evidence regarding the interaction between individual psychological factors and organizational climate in explaining Generation Z employee performance in the banking sector.